The Impact of Human Resource Quality and Business Capital on the Growth of MSMEs in Suruh Village, Trenggalek Regency - Sulchan, Moch (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This research is driven by the significance of Micro, Small, and Medium Enterprises (MSMEs), which are regarded as critical due to their capacity to employ individuals and provide economic assistance to a large population. However, despite their vitality, MSMEs are not exempt from the challenges they encounter, which include inadequate business capital and substandard human resources. The primary objective of this study is to investigate the impact of human resource quality and business capital on the growth and progress of micro, small, and medium-sized enterprises. This study employs a quantitative methodology and is of the associative variety. The data were gathered via a questionnaire employing the purposive sampling procedure. The investigation utilized a sample size of 135 participants, specifically MSME actors residing in Suruh Village, Suruh District, Trenggalek Regency. Subsequently, the questionnaire data underwent analysis via multiple linear regression, which had previously passed the validity, reliability, and classical assumption tests. The t and f tests were subsequently computed. Research findings indicate that: business capital and the Quality of Human Resources have a substantial positive impact on the growth and progress of micro, small, and medium enterprises, respectively